Strategic advantages of good supplier relations in the Indian automobile industry - Khare, Anshuman
The author examines industry/supplier relationships in the automobile industry, demonstrating the strategic advantages of Indo/Japanese collaboration. He also analyses similarities and differences between situations in the two countries.
This paper deals with supplier relationships in the Indian automobile industry. Here I have attempted to draw attention to the strategic advantages being generated by the Indo-Japanese collaboration, Maruti Udyog Limited (MUL), due to effective management of supplier relationships. Having Suzuki Motors as its collaborator, MUL's strategy is very much like the Japanese company's. In general, it could be said that the Japanese method is giving good results for MUL as the Indian market slowly opens up to international competition. MUL can depend on its suppliers whom it has groomed over the last 12-13 years while countering competition. The paper goes further, to analyse the similarities and the dissimilarities between the Indian and the Japanese situations. Given these differences and similarities in the Indian and Japanese situations and supplier relations management, the paper highlights some points which go a long way in establishing sound business relationships.
Keywords: Automobile industry--India.